Maple leaf harvest : a Mystic Creek novel - Anderson, Catherine (Adeline Catherine) (Anderson, Catherine (Adeline Catherine). Mystic Creek novel., 2021)
Seeking refuge in Mystic Creek, Oregon, Lane Driscoll, plagued by strange dreams, discovers, with the help of the town psychologist, that she has a twin sister who may be in danger, and as they race against time to find her, romance blossoms between them.